The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13058-015-0627-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of PALB2 mutations in Australian familial breast cancer cases and controls

Abstract: IntroductionPALB2 is emerging as a high-penetrance breast cancer predisposition gene in the order of BRCA1 and BRCA2. However, large studies that have evaluated the full gene rather than just the most common variants in both cases and controls are required before all truncating variants can be included in familial breast cancer variant testing.MethodsIn this study we analyse almost 2000 breast cancer cases sourced from individuals referred to familial cancer clinics, thus representing typical cases presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 48 publications
(58 reference statements)
1
38
2
Order By: Relevance
“…PALB2 encodes a BRCA2‐interacting protein in the DNA repair process . Deleterious PALB2 mutations were found in familial breast cancer with a prevalence of about 1% to 4% and .1% to 1% in unselected breast cancer . In our study, only 1 novel deleterious mutation (.34%) was detected in PALB2 .…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…PALB2 encodes a BRCA2‐interacting protein in the DNA repair process . Deleterious PALB2 mutations were found in familial breast cancer with a prevalence of about 1% to 4% and .1% to 1% in unselected breast cancer . In our study, only 1 novel deleterious mutation (.34%) was detected in PALB2 .…”
Section: Discussionmentioning
confidence: 43%
“…The PALB2 c.3054G>C variant was a recurrent mutation found in 3 cases (1.03%) in this study. This variant has also been observed in Australian patients (1/1998), Korean patients (1/235), Asian population in Malaysia and Singapore (1/122) . The prevalence of this variant ( PALB2 c.3054G>C) in Chinese population seemed to be higher than other ethnic groups.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, truncating mutations in PALB2 were also detected in Chinese familial breast cancer, although the relative risk has not been estimated . These studies simultaneously identified many non‐synonymous missense variants in PALB2 , but there was no evidence that these variants were associated with breast cancer predisposition . In our study, no deleterious truncating variant was identified, and the allele counts of the observed missense variants were not statistically different from that in HGVD (Tables and ).…”
Section: Discussioncontrasting
confidence: 47%
“…Many studies previously reported that mutations in the PALB2 gene showed evidence of being correlated with a significantly increased risk of breast cancer [9,10,11,12], especially hereditary breast cancer [13,14]. Mutations in the PALB2 gene confer a doubled breast cancer risk with moderate-to-low penetrance [15].…”
Section: Discussionmentioning
confidence: 99%